Responses of soil enzyme activities and bacterial community structure to different hydrological regimes during peatland restoration in the Changbai Mountain, northeast China - Wang, Ming; Xu, Shangqi; Wang, Shengzhong; Chen, Cong; Wang, Yuting; Liu, Lei (Frontiers in Microbiology, 2022)
Appropriate hydrological management is critical for peatland restoration. An important prerequisite for peatland restoration is a recovery of soil biological processes. However, little is known about the effects of different hydrological management practices on soil biological processes during peatland restoration. In this study, the variations in soil properties, enzyme activities, and bacterial communities across different peatlands, namely natural peatland (NP), peatland restored under high water level (HR), peatland restored under alternating high-low water level (HLR), peatland restored under low water level (LR), and degraded peatland (DP), in the Changbai Mountains were investigated. Results showed that soil organic carbon, soil water content, and total nitrogen in NP were significantly higher than those in restored and degraded peatlands, and these soil properties in restored peatlands increased with the water level. The activities of soil hydrolases including β-1, 4-glucosidase, β-1, 4-n-acetylglucosidase, and acid phosphatase in NP were higher than in restored and degraded peatlands, while the activity of polyphenol oxidase in NP was the lowest. In restored peatlands, all measured enzyme activities decreased with the decline in water level. Both bacterial diversity and richness in NP were the lowest, while the highest diversity and richness were observed in HR. Redundancy analysis indicated that soil organic carbon, water level, soil water content, total nitrogen, and pH were the most important factors that affected the soil enzyme activities and bacterial community. Our findings give insight into the effects of different hydrological regimes on soil biological processes during peatland restoration. Maintaining a high water level early in the restoration process is more beneficial to restoring the ecological functions of peatlands than other hydrological management practices.